Burnout and patient safety perceptions among surgeons in the United Kingdom during the early phases of the coronavirus disease 2019 pandemic: A two-wave survey. Issue 2 (May 2023) - Al-Ghunaim, Tmam; Johnson, Judith; Biyani, Chandra S; Yiasemidou, Marina; O'Connor, Daryl B
Background: Surgeons in the UK report high burnout levels. Burnout has been found to be associated with adverse patient outcomes but there are few studies that have examined this association in surgeons and even fewer which have examined this relationship over time. Purpose: The main aim was to examine the relationships between surgeon burnout and surgeons' perceptions of patient safety cross-sectionally and longitudinally. The secondary aim was to test whether surgeons' burnout levels varied over the first six months of the coronavirus disease 2019 pandemic. Methods: This paper reports data from a two-wave survey (first wave from 5 May and 30 June 2020, the second wave 5 January to 30 February 2021). The dataset was divided into a longitudinal group (for surgeons who responded at both the time points) and two cross-sectional groups (for surgeons who responded at a one-time point, but not the other). Results: The first key finding was that burnout was associated with patient safety outcomes measured at the same time point (Group 1 = 108, r =  0.309, p < 0.05 and Group 2 = 84, r =  0.238, p < 0.05). Second, burnout predicted poor patients' safety perceptions over time, and poor patient safety predicted burnout over time (Group 3 = 39, p < 0.05). Third, burnout increased between the first and second surveys ( t = -4.034, p < 0.05). Conclusion: Burnout in surgeons may have serious implications for patient safety. Interventions to support surgeons should be prioritised, and healthcare organisations, surgeons and psychological specialists should collaborate on their development.